Hyperbaric Oxygen in Otorhinolaryngology: Current Concepts in Management and Therapy - Andrea Collettini; Federica Zoccali; Christian Barbato; Antonio Minni (Oxygen, 2024)
Background: In otorhinolaryngology and head and neck surgery, oxygen is a therapeutic tool used for various pathologies. Oxidative stress is the imbalance between the production of free radicals (ROS) and the antioxidant capacity of the body, which can represent the pathogenesis of several pathologies or contribute to their worsening. This narrative review aims to analyze the benefits, indications, and side effects of hyperbaric oxygen therapy (HBOT) in different head and neck disorders. Methods: The search was carried out on multiple electronic databases such as PubMed and Google Scholar, and prospective, randomized, and reviewed studies were analyzed from January 1982 to February 2024. Results and Conclusions: The most common tools used to manage oxidative stress in the ear, nose, and throat (ENT) field are continuous positive airway pressure (CPAP) and HBOT. A common ENT pathology, while the latter can be used for osteoradionecrosis treatment in head and neck cancer patients, infections, malignant external otitis, head and neck reconstruction, facial cosmetic surgery, and among patients with sudden sensorineural hearing loss. From our analysis, it emerged that HBOT is a currently used effective therapy in various ENT pathologies’ treatment, alone or in association with other treatments; it can guarantee functional recovery and healing depending on the type of pathology for which it is used and on its severity.